Student Ethics in Learning Perspectives of Kiai Hajj Muhammad Zaini Sekumpul Martapura - Barni, Mahyuddin; Yusran, Muhammad (IAIN Samarinda, 2019)
Students are a component of the education system. It will not be called education if the student is not in it. To succeed in education (learning), many conditions must be considered; one of which is ethics or manners. In the context of Islamic education, ethics or manners for a student is very important. It is difficult for a student to succeed in education if he is not ethical or civilized.Â Even if he succeeded in education or in learning, then his knowledge was not a blessing or not useful for others or a cause of destruction for himself. This paper aims to describe the ethics of a student who is learning according to the perspective of a religious figure so that he is successful in his learning. This paper used documentary techniques. The data of this paper obtained from the recordings of lectures delivered by Kiai Haji Muhammad Zaini during his lifetime and juxtaposed with the book read by him. Student ethics according to Kiai Hajj Muhammad Zaini is that a student should always expect and ask his teacher to always pray for him, use the time for useful activities, repeat lessons at home and ask back to the teacher related lessons that are still vague for him, clean the intention when looking for knowledge that is only because of Allah SWT, revive religion, keep the Islamic shari'a in order to remain there, intend the knowledge gained will be practiced, always do good deeds and adorn themselves with praiseworthy qualities, get used to getting up at night to worship Allah and ask Allah in order to give him useful knowledge and other virtues, respect his teacher zahir (external) and bathin (inner), not make friends or be close with people who are not in good morals (immoral perpetrators and other deeds), do not use the knowledge they get to debate or pilgrimage, always trying to be close to Allah SWT, accustom to ablution before learning, always reading the Qur'an, always correcting the five senses of sin in order to quickly understand the science of religion.